Solution of fully Fuzzy Linear Fractional Programming Problem-A Simple Approach - Loganathan, T.; Ganesan, K. (IOP conference series. Materials Science and Engineering, 2021)
In this paper, we discuss fully fuzzy linear fractional programming (FFLFP) problems under fuzzy nature with triangular fuzzy numbers. We recommend a simple method for the solution of FFLFP problems which preserves the fuzzy nature of the problem. The efficiency of the method proposed is illustrated with an example.